Formação político-educativa do Movimento dos Trabalhadores Rurais Sem Terra (MST) no contexto do Governo Lula (2003 a 2010) - COUTINHO, Célio Ribeiro (www.teses.ufc.br, 2015)
COUTINHO, Célio Ribeiro. Formação político-educativa do Movimento dos Trabalhadores Rurais Sem Terra (MST) no contexto do Governo Lula (2003 a 2010). 2014. 228f. – Tese (Doutorado) – Universidade Federal do Ceará, Programa de Pós-graduação em Educação Brasileira, Fortaleza (CE), 2014. === Submitted by Márcia Araújo (marcia_m_bezerra@yahoo.com.br) on 2015-01-19T14:26:09Z No. of bitstreams: 1 2014_tese_crcoutinho.pdf: 2213239 bytes, checksum: c71581544d63baa72a25d01adb445eeb (MD5) === Approved for entry into archive by Márcia Araújo(marcia_m_bezerra@yahoo.com.br) on 2015-01-19T15:26:06Z (GMT) No. of bitstreams: 1 2014_tese_crcoutinho.pdf: 2213239 bytes, checksum: c71581544d63baa72a25d01adb445eeb (MD5) === Made available in DSpace on 2015-01-19T15:26:07Z (GMT). No. of bitstreams: 1 2014_tese_crcoutinho.pdf: 2213239 bytes, checksum: c71581544d63baa72a25d01adb445eeb (MD5) Previous issue date: 2014 === This work, the result of research conducted by the Movement of Landless Rural Workers (MST in Portuguese), was based on assumptions of Marx, Gramsci and Freire. The main objective consisted in studying the process of political-educational training of the MST, in its relationship with the Government Lula context (2003-2010). As theoretical and methodological apparatus, we opted for the use of the design of the dialectical method (analysis and synthesis); phenomenology (phenomenon description); content analysis (production of new meanings); content aggregation (associations analysis for categories and trends in the data); and grounded theory (theoretical scheme of production). In this type of qualitative research, we started with a case study in the design of participant and ethnographic research and used a quantitative instrumental. There were the option research techniques: categorical analysis of the thematic type (dismemberment of texts into categories and analog reunification); association analysis (identification of component analysis and categories); questioning technique (formulation of questions to examine the data); comparisons technique (identification and development of categories). Were adopted observation techniques and semi-structured interviews (63 interviews with internal and external members to MST). In the methodology yet were made use of tables, figures and mathematical formulas that facilitated the organization and analysis of empirical data. Among the findings of the survey stood out: the Descent and the MST Accommodation Pedagogy, phenomena that occurred simultaneously. The process of Descent was determined by the dependence of Government Policies and the Demobilization by Capital. The dependence resulting from the decrease of the Political and Organizational Power and the Institutionalization of the increase stemmed from the financial dependence and bureaucratization of the militancy work. Demobilization by Capital Disqualification determined by the Worker’s Party (Partido dos Trabalhadores – PT, in Portuguese) and demobilization by the government was based on the strength of capital, which dominated the state, the Lula’s government and the PT. The categorical composition of demobilization by Capital became more decisive of Descent than dependence on government policies. Based on the same determinations of Descent, identified the presence of Pedagogy Accommodation produced by MST Training Tying the Capital and Training for Conformation to government policies. This subordination resulting from the Training Compliance to Government Policies and Training Adaptation to Disqualification of the PT, resulted from the training environment for domination, provided by capitalist relations present in the state, the government and the PT. Originated Conformation of The Training Institutionalization and Training for Pacification was based on the bureaucratization of the work, financial dependence and decreased radical militancy. These factors result from the weakening of the role of organic intellectual of the MST. Part of militancy did resistance to the political strategy adopted which prevented the total loss of their political autonomy in government. Given the weakening of the Counter-Hegemonic MST fight, is presented as a suggestion to the Movement: a review of its policy strategy to deal with governments of the same political field and resumed the role in the struggle for land reform and for a socialist society. === Este trabalho, resultante de pesquisa realizada junto ao Movimento dos Trabalhadores Rurais Sem Terra (MST), fundamentou-se nos pressupostos de Marx, Gramsci e Freire. O objetivo central constituiu-se em estudar o processo de formação político-educativa do MST, na sua relação com o contexto do Governo Lula (2003 a 2010). Como aparato teórico-metodológico, optou-se pelo uso da concepção do método dialético (análise e síntese); fenomenologia (descrição do fenômeno); análise de conteúdo (produção de novos significados); associação de conteúdos (análises das associações para determinação de categorias e tendências nos dados); e teoria fundamentada (produção de esquema teórico). Nesta pesquisa de tipo qualitativa, partiu-se de um estudo de caso na concepção de pesquisa participante e etnográfica e utilizou-se um instrumental quantitativo. Fez-se opção pelas técnicas de pesquisa: análise categorial do tipo temática (desmembramento dos textos em categorias e reagrupamento analógico); análise de associações (identificação dos componentes de análise e das categorias); técnica de questionamentos (formulação de questões para examinar os dados); técnica de comparações (identificação e desenvolvimento das categorias). Adotaram-se técnicas de observação e de entrevistas semiestruturadas (63 entrevistas com membros internos e externos ao MST). Na metodologia fez-se ainda uso de quadros, figuras e fórmulas matemáticas, que facilitaram a organização e análise dos dados empíricos. Entre os achados da pesquisa, destacaram-se: o Descenso e a Pedagogia da Acomodação do MST, fenômenos que ocorreram simultaneamente. O processo de Descenso determinou-se pela Dependência do das Políticas do Governo e pela Desmobilização pelo Capital. A Dependência decorrente da Diminuição da Força Político-Organizativa e do Aumento da Institucionalização originou-se da dependência financeira e da burocratização do trabalho da militância. A Desmobilização pelo Capital determinada pela Descaracterização do PT e pela Desmobilização pelo Governo teve como fundamento a força do capital, que dominou o Estado, o Governo Lula e o PT. A composição categorial da Desmobilização pelo Capital tornou-se mais determinante do Descenso do que a Dependência das Políticas do Governo. Com base nas mesmas determinações do Descenso, identificou-se a presença da Pedagogia da Acomodação produzida pela Formação do MST para Subordinação ao Capital e Formação para a Conformação às Políticas do Governo. Tal Subordinação, decorrente da Formação para Adequação às Políticas do Governo e da Formação para Adequação à Descaracterização do PT, resultou do ambiente de formação para a dominação, proporcionado pelas relações capitalistas presentes no Estado, no Governo e no PT. A Conformação originada da Formação para Institucionalização e da Formação para Pacificação teve como base a burocratização do trabalho, dependência financeira e diminuição da radicalidade da militância. Esses fatores decorrem do enfraquecimento do papel de intelectual orgânico do MST. Parte da militância fez resistência à estratégia política adotada o que impediu a perda total de sua autonomia política nesse governo. Diante do enfraquecimento da luta Contra-Hegemônica do MST, apresenta-se como sugestão ao Movimento: revisão de sua estratégia política para enfrentar governos do mesmo campo político e retomada do protagonismo nas lutas pela reforma agrária e por uma sociedade socialista.